2022
DOI: 10.1002/nme.7188
|View full text |Cite
|
Sign up to set email alerts
|

A micropolar shell model for hard‐magnetic soft materials

Abstract: Hard-magnetic soft materials (HMSMs) are particulate composites that particles with high coercivity are dispersed in a soft matrix. Since applying the magnetic loading induces a body couple in HMSMs, the resulting Cauchy stress is predicted to be asymmetric. Therefore, the micropolar continuum theory can be employed to capture the deformation of these materials. On the other hand, the geometries and structures made of HMSMs often possess small thickness compared to the overall dimensions of the body. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…A model based on micropolar continuum shell theory (where each material particle was coupled with a microstructure that can undergo micro-rotation) was proposed and verified with FE simulations [289,322]. Xing and Yong [323] investigated the viscoelastic effects of hMSMs in finite deformation and the instabilities they induce using a numerical model with a micro-mechanically motivated formulation.…”
Section: Microstructurally-guided Homogenization Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A model based on micropolar continuum shell theory (where each material particle was coupled with a microstructure that can undergo micro-rotation) was proposed and verified with FE simulations [289,322]. Xing and Yong [323] investigated the viscoelastic effects of hMSMs in finite deformation and the instabilities they induce using a numerical model with a micro-mechanically motivated formulation.…”
Section: Microstructurally-guided Homogenization Modelsmentioning
confidence: 99%
“…The prevalent method in studying magneto-mechanical problems often assumes an ideal homogeneous magnetic field [272,289]. Yet, relying solely on this idealization might lead to significant disparities from observations in real setups.…”
Section: Importance Of Accounting For Magnetic Bcs and Surrounding Sp...mentioning
confidence: 99%
“…Their findings suggest that when modeling incompressible materials, the F-bar formulation can be computationally expensive, and the mixed displacementpotential formulation is somewhat sensitive to changes in the modulus. In the context of thin HMS materials, Dadgar-Rad and Hossain [329] developed a micro-based shell model for simulating their deformation. They extended the 7-degrees of freedom (DoF) formulation of Sansour [330] to a 10-DoF formulation scheme that accounted for the microrotation of the microstructure.…”
Section: Temperature Effectmentioning
confidence: 99%
“…In the context of thin HMS materials, Dadgar–Rad and Hossain [ 329 ] developed a micro‐based shell model for simulating their deformation. They extended the 7‐degrees of freedom (DoF) formulation of Sansour [ 330 ] to a 10‐DoF formulation scheme that accounted for the microrotation of the microstructure.…”
Section: Modeling Of Mresmentioning
confidence: 99%
“…Notably, Sun et al [12] have demonstrated that an augmentation in magnetic flux leads to smoother frequency response peaks, attributed to an amplified damping effect within the structure. Several other authors have investigated the viscoelastic modeling of MREs and their application [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%